Influencing factors of willingness to purchase long-term care insurance for employees in Shenzhen, China - AN, RAN; SHI, YI; GUO, JIAN; YANG, XIAOSHENG (Pacific International Journal, 2022)
Purpose: In the early stage of Shenzhen’s long-term care insurance pilot, the awareness, demand, and purchase intention of Shenzhen residents about long-term care insurance and their influencing factors were investigated to provide a basis for improving the government’s long-term care insurance system. Methods: A structured questionnaire survey was carried out on the Shenzhen employee medical insurance participants. Descriptive statistics, Chi-square test, and Order logistic regression were performed. Results: 298 respondents (female 57.7%), filled out the questionnaires. About 73% of the respondents have never heard of long-term care insurance. Respondents’ average demand of long-term care was 3.06, which was the general level. The 161(54%) respondents’ willing to purchase long-term care insurance and the main influencing factors of purchase willingness are self-assessment of long-term care possibility, monthly income, annual family income and their willingness to pay for long-term care services. Conclusions: Respondents lack risk awareness and have low awareness of long-term care insurance; their effective demand for long-term care insurance is insufficient, but the demand for long-term care services is specialized and diversified, and their intention to purchase long-term care services is slightly higher than purchase intention of long-term care insurance. Recommendations: Departments at all levels should work together to strengthen the publicity of long-term care insurance to raise awareness among the population, improve the quality of practitioners, and improve the elderly care service system to meet the needs of the specialized and diverse population, and broaden financing channels to deal with the risk that the population is not willing to buy.